Economic development and environmental protection: The need for more equal income distribution for achieving sustainable development from an economic and fairness perspective - Joost Platje (Economic and Environmental Studies (E&ES), 2013)
In this paper, the relation between the equality of income distribution and sustainable development is discussed. This issue is elaborated using theories of justice of John Stuart Mill, John Roemer, John Rawls and Amartya Sen.
Keywords: 330; sustainable development; economic development; environmental protection; theories of justice; income distribution